The Influence of Instructional Leadership and Data-Based Decision Making on Teacher Performance - Misriyadi; Tri Yuni Hendrowati; Fatqul Hajar Aswad (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
One-way learning in schools has the potential to lead to dogmatization because it positions the teacher as the sole source of truth, resulting in students being passive and lacking critical thinking skills. This condition is related to the principal’s leadership role and suboptimal decision-making patterns. This study aims to analyze the influence of the principal’s instructional leadership and data-based decision-making on the performance of public elementary school teachers in Padang Cermin District. The study used a quantitative approach with a survey method. Data were collected through closed-ended questionnaires that had been tested for validity and reliability, then analyzed using multiple linear regression. The results showed that the principal’s instructional leadership significantly influenced teacher performance. Data-based decision-making also significantly influenced teacher performance. Simultaneously, both variables had a positive and significant effect on teacher performance. These findings emphasize the importance of strengthening instructional leadership and systematically utilizing data to improve teacher performance and encourage more participatory learning in elementary schools. Keywords: Instructional Leadership, Decision-Making, Teacher Performance